Specificities of the workflow and evaluation of the working conditions of the working main professions of industrial rubber and technology production - Rakhmetova, A.M.; Alshynbekova, G.K.; Tusupbekova, G.A. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
In the available literature there is a large number of diverse works on the assessment of the labor process and working conditions of industrial rubber production. At the same time, it is of interest and there is a practical need for a sanitary-hygienic assessment of the working conditions of workers in basic occupations who are in contact with chemical substances of a general toxic and irritant action during production. The production of industrial rubber products is based on a multistage intermittent technological process using numerous chemicals of the second, third and fourth classes of toxicity. During a work shift, production personnel is exposed to fractional and short-term exposure to toxic substances, therefore, the toxic effects of chemicals used in the industrial rubber industry to workers are enhanced, which was the purpose of the study. To assess the work process and the working conditions of the workers of the main occupations of industrial rubber production, the study of air dustiness, microclimate, and relative humidity was conducted. As a result of the research, it was established that one of the unfavorable production factors at the factory of the industrial rubber products is dustiness, air pollution, overcooling, overheating and considerable physical stress.
Техникалық резеңке өндірісіндегі негізгі кәсіби жұмысшылардың еңбек жағдайлары мен еңбек үрдісінің ерекшеліктерін бағалау
Особенности трудового процесса и оценка условий труда рабочих основных профессий резинотехнического производства
Keywords: industrial rubber production; technological process; toxic chemicals; dust formation; gas formation